Prevalence of gastrointestinal nematodiasis and coccidiosis in goats from three selected farms in Terengganu, Malaysia - Mat Yusof, Afzan; Md Isa, Muhammad Lokman (Elsevier BV, 2016)
Objective To reveal the prevalence of gastrointestinal nematodiasis, Trichostrogylus, Haemonchus, Strongyloides and Trichuris and coccidiosis, mainly Eimeria in kids, yearlings and adult goats. Methods A total of 287 goat faecal specimens were randomly collected from three farms in Kuala Terengganu, Setiu and Besut. Results Prevalence of coccidiosis (89.2%) was significantly higher (P < 0.05) than gastrointestinal nematodiasis (52.3%). Gastrointestinal nematodes (GINs) were found in 37.0% kids, 63.5% yearlings and 53.3% adults. Identification of GINs revealed the predominance of Strongyloides (45.6%) followed by Trichostrogylus (12.9%), Haemonchus (11.8%) and Trichuris (8.7%) in all groups whereby the adult goats recorded the highest infections of Trichostrogylus (20.5%), Haemonchus (10.6%), Strongyloides (51.5%) in all groups. The age-specific intensity for Eimeria was in following order: kids (92.6%), adults (86.6%) and yearlings (51.5%) and the difference was not significant (P > 0.05). The concurrent infections between GINs and Eimeria were 67.94% in all groups. Polyparasitisms of Trichostrongylus (17.4%), Haemonchus (15.15%) and Strongyloides (40.4%) with Eimeria had infected most adult goats. Dual infections of Trichostrongylus with Eimeria and Trichuris with Eimeria were significantly higher in adults than yearlings and kids (P < 0.05).